After the colonial: Tina Rimmer the Borneon artist - Sim, Chee Cheang; Rosalind Goh Sy Lind; Ismail Ibrahim (American Scientific Publishers, 2018)
James Williamson in his 2nd edition of A Short History of British Expansion (1931) drew his readers attention to the dwindling numbers of European colonials particularly the British colonials in the colonies which numbered 1.5 million in 1921 and then 1.4 million in December 192715. Imperialism was at its closure after the world war and the world was in depression. Those who lived after the war returned home even those who were at the fringes of the British colonies. This article explores the social transformation of post imperial colonials who did not return after imperialism especially in the fringes of non-white former colonies like the North Borneo of Malaysia. The question that begs is the resistance or insistence of the imperial mindset of these colonials who did not return home after imperialism. Since there are few who are still alive to answer this question, the one important respondent that has been identified in this research is Tina Rimmer or Mary Christina Rimmer née Lewin, a much loved Borneo[n] artist who  will turn a 100 in August 20171.